Green preparation of thermal and solvent resistant poly (tetrafluoroethylene‐co‐perfluoropropylvinyl ether) hollow fiber membrane for organic solvent recycling. Issue 32 (20th April 2021) - Chen, Kaikai; Shu, Xi; Xiao, Changfa; Zhang, Tai; Ling, Haoyang
Abstract: So far, the organic solvent recycling still has great challenges. Herein, the thermal and solvent resistant poly (tetrafluoroethylene‐co‐perfluoropropylvinyl ether) (PFA) hollow fiber membranes (TS‐PFA HFMs) were continuously designed by on‐line compound technique for organic solvent recycling. The experiment results indicated that the increased sintering temperature brought about the porous surface and loose internal cavity structures. Importantly, the membrane exhibited the excellent thermal resistance at 70°C working condition. Furthermore, part of the poly (vinyl alcohol) was retained in the membrane which was competent to create synergistic effects, and endowed the membrane with not only favorable elasticity but also remarkable hot water resistance. Finally, the excellent organic solvent recycling ability of the membrane was demonstrated in simulated non‐aqueous solvent dyeing system. Specifically, no organic solvents or other hazardous substances were used during the fabrication process, which can realize the green preparation of the membrane. Abstract :